Optimisation of Rice Production on Tidal Lands through Ameliorant Technology - Mulyadi, Mulyadi; Sutikarini, Sutikarini (International Journal of Multi Discipline Science (IJ-MDS), 2025)
The research aims to identify organic ameliorant technology for increasing rice production in tidal areas. This research used a Completely Randomized Design method with 7 treatment levels were repeated 3 times. Ameliorant technology includes: A0 (Dolomite 10 tons/ha) A1 (husk charcoal 10 tons/ha), A2 (rice straw at a dose of 10 tons/ha), A3 (cow manure at a dose of 10 tons/ha), A4 (husk charcoal 10 tons/ha + Trichoderma 600 kg/ha), A5 (rice straw 10 tons/ha + Trichoderma 600 kg/ha), and A6 (cow manure at a dose of 10 tonnes/ha + Trichoderma 600 kg/ha). The rice seeds used were the Inpari 24 variety. The results of the research showed that the Amelioran technology treatment had no significant effect on plant growth observations, namely, plant height and number of rice tillers. Treatment A3 (10 tons/ha cow manure) had the highest average plant height of 102.52 cm. Treatment A6 (cow manure 4 kg/plot + Trichoderma 240 g) had the lowest plant height, namely 89.93 cm. Treatment A1 (Charcoal husk 10 tons/ha) had the highest average number of tillers at 35.3 tillers. Treatment A6 (4 kg cow manure + 240 g Trichoderma/plot) had the lowest number of calves, namely 21.7. This was thought to be due to the framing effect, namely complex interactions between living organisms in the soil, both those in cow manure and Trichoderma. The negative framing effect that occurs is that plant growth is hampered, and some plants have stem rot, which causes some plants to wilt and die.